Design and graphic communication health communication: the social graphic expression of the disease - Juarez Pierce, Maria del Socorro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2016)
The work is part of studies for the Get the degree of PhD in Mexico. Thereof are intended widen the theoretical and practical relations between the design of graphic communication and health communication. What else a through observation of the graph of the disease posters diabetes health . In this sense, figurative relationships found in the historical, artistic and social expression of diseases of different cultures and eras are studied; as these may influence or clashing in the figuration of contemporary mexican cartels Health. To analyze the correlation, is important to place attention on six works of art. Related to diseases in different contexts; as well as, three health posters diabetes. Released by the Ministry of Health (SSA) and the Alliance for Health Food. In the samples, figurations of the phases of individual and social life, being experienced people to suffer diseases are compared.